Evaluate ∫[e^(3x)/(1+e^x)]dx
Let
u = (1+e^x)
(u - 1) = (e^x)
du = (e^x)dx
(1/(e^x))du = dx
thus
∫[e^(3x)/(1+e^x)]dx = ∫[e^(3x)/u](1/(e^x))du
∫[e^(3x)/(1+e^x)]dx = ∫[e^(3x-x)/u]du
∫[e^(3x)/(1+e^x)]dx = ∫[e^(2x)/u]du
∫[e^(3x)/(1+e^x)]dx = ∫[(e^x)²/u]du
recall (u - 1) = (e^x)
∫[e^(3x)/(1+e^x)]dx = ∫[(u - 1)²/u]du
expand: (u - 1)² = (u² - 2u + 1)
∫[e^(3x)/(1+e^x)]dx = ∫[(u² - 2u + 1)/u]du
∫[e^(3x)/(1+e^x)]dx = ∫[u²/u - 2u/u + 1/u]du
∫[e^(3x)/(1+e^x)]dx = ∫[u - 2 + 1/u]du
∫[e^(3x)/(1+e^x)]dx = ∫[u]du - ∫[2]du + ∫[1/u]du
∫[e^(3x)/(1+e^x)]dx = (1/2)u² - 2u + (ln u) + C
recall u = (1+e^x)
∫[e^(3x)/(1+e^x)]dx = (1/2)(1+e^x)² - 2(1+e^x) + (ln (1+e^x)) + C <--- answer
Note simplify further if you want to.